Women's Empowerment to Support Public Health and Poverty Reduction as Community Development (Herbaman Program) by PT Perusahaan Gas Negara (Sales and Operation Region III) in Tambak Kalisogo Village, East Java - Rio Zakarias W; Sigit Tri Hartanto Sukamto; Tri Apriansyah (International Journal of Economics, Business and Innovation Research, 2024)
Efforts to reduction poverty and reduce social inequality in Indonesia, especially in East Java, still face major challenges, such as the high level of poverty that has an impact on public health. In Tambak Kalisogo Village, Sidoarjo, the establishment of the Family Medicinal Plants Self-Help Group (Asman Toga) by the local government and the support of PT Perusahaan Gas Negara through the HERBAMAN programme aims to improve health and economic welfare through women's empowerment. This qualitative study used purposive sampling to understand the impact of the programme on family health and economy. The results show that the HERBAMAN programme succeeded in increasing household income, reducing fire risk, and improving the environment. This success was supported by the co-operation of various parties, showing that community synergy and innovation can bring sustainable positive change.